HEALTH SAFETY ENVIRONMENT: A CRITICAL SUCCESS FACTOR FOR OPERATIONAL PERFORMANCE - Amos, N. B., Dogo, E. B. & Duruanyanwu, A. B. (International Journal of Research Science and Management, 2020)
The study sought to investigate the effect of health safety environment on the operational performance of Astral waters Nigeria limited, Lagos State. Although, the manufacturing sector is perceived to be the real life of the economy and the engine that drives economic growth in the country, the increased number of work-related injuries and accidents has increased operational cost for the firm thereby leading to a decline in the operational performance of the firm. A cross sectional survey research design was adopted, and a survey of 40 employees was carried out using a validated questionnaire. The findings showed that health safety environment has a positive and significant effect on operational performance of the sampled firm. The study therefore recommends that manufacturing firms and others along the same value chain must strive to adapt and sustain health safety environment that will ensure environmental standards, show commitment to safety by establishing a positive culture, ensure employees are actively involved and participate in safety-related activities that will ensure workers have a sense of safety while carrying out their tasks, in order to enhance the firms’ operational performance.